Intravascular Papillary Endothelial Hyperplasia: The Diagnostic Challenges - P, Kaushika; Thanka, J; Lilly, S Mary; Gali, Vinutha (Annals of Pathology and Laboratory Medicine, 2021)
Masson’s tumor or intravascular papillary endothelial hyperplasia is a benign lesion of the skin and subcutaneous tissue. It is due to reactive proliferation of endothelial cells with papillary formations related to a thrombus. It poses an interesting diagnostic differential as the clinical signs and symptoms are nonspecific. The diagnosis is based on histopathology. We report a case of Masson’s hemangioma occurring on the right ring finger.